Heavy metals Assessment of Temple Ponds in Kanchipuram, Tamil Nadu, India. Issue 1 (October 2020) - Meenakshi, P; Sriram, G
Abstract: Heavy metals are a major environmental pollutant, they are slow, non-degradable material it affects the aquatic ecosystem. Heavy metal pollutant molecules arrive the pond water through anthropogenic activities, domestic waste, hospital wastes and temple wastes. The investigation was designed to study the seasonal spreading of specific heavy metals Iron (Fe), Copper (Cu), Lead (Pb), Arsenic (As) and Zinc (Zn)) in pond water. Seventeen pond water samples were collected during pre- monsoon (March 2017) and post monsoon (January 2018) period. The concentration of Iron in the pre monsoon greater than class A limit. The concentration of other prescribed heavy metal was less than central pollution control board standards in both the season. Hence pond water having a negligible amount of heavy metal pollution. This environmental observing and valuation research useful for managing and planning for the protection of pond.